Assessment of cardiac‐driven liver movements with filtered harmonic phase image representation, optical flow quantification, and motion amplification. Issue 4 (28th November 2018) - Hahn, Stephan; Absil, Julie; Debeir, Olivier; Metens, Thierry
Abstract : Purpose: To characterize cardiac‐driven liver movements using a harmonic phase image representation (HARP) with an optical flow quantification and motion amplification method. The method was applied to define the cardiac trigger delay providing minimal signal losses in liver DWI images. Methods: The 16‐s breath‐hold balanced‐SSFP time resolved 20 images/s were acquired at 3T in coronal and sagittal orientations. A peripheral pulse unit signal was recorded. Cardiac‐triggered DWI images were acquired after different peripheral pulse unit delays. A steerable pyramid decomposition with multiple orientations and spatial frequencies was applied. The liver motion field‐map was derived from temporal variations of the HARP representation filtered around the cardiac frequency. Liver displacements were quantified with an optical flow method; moreover the right liver motion was amplified. Results: The largest displacements were observed in the left liver (feet‐head:3.70 ± 1.06 mm; anterior–posterior: 2.35 ± 0.51 mm). Displacements were statistically significantly weaker in the middle right liver (0.47 ± 0.11 mm; P = 0.0156). The average error was 0.013 ± 0.022 mm (coronal plane) and 0.021 ± 0.041 mm (sagittal plane). The velocity field demonstrated opposing movements of the right liver extremities during the cardiac cycle. DWI signal loss was minimized in regions and instants of smallest amplitude of both velocity and velocity gradient. Conclusion: Cardiac‐driven liver movements were quantified with combined cardiac frequency‐filtered HARP and optical flow methods. A motion phase opposition between right liver extremities was demonstrated. Displacement amplitude and velocity were larger in the left liver especially along the vertical direction. Motion amplification visually emphasized cardiac‐driven right liver displacements. The optimal cardiac timing minimizing signal loss in liver DWI images was derived.